Kerentanan kanak-kanak Malaysia terhadap pengantunan seksual dalam talian - Asmi Asmidar Zainal Rashid,; Mohammad Rahim Kamaluddin,; Suzaily Wahab,; Dayang Anita Abdul Aziz,; Zarina Abdul Latiff,; Balan Rathakrishnan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was conducted to examine the vulnerability of Malaysian children towards online sexual grooming by ascertaining the level of vulnerability and the relationships with social media profiles and demographical factors. To achieve the objectives of this study, a quantitative method using a cross-sectional research design with the aid of electronic questionnaire via Google Form was used to gather the data. A total of 205 Malaysian children from the age of 10 to 17 years old participated in this study with their parents’ consent. Based on the analyses of the items, it was found that each child was vulnerable towards sexual grooming at different levels. This study also found that the frequency of social media usage was directly correlated with online sexual grooming vulnerability (r = 0.14, p = 0.05) and age of the respondents (r = 0.20, p = 0.006). Children with more social media accounts were also found to be more vulnerable towards online sexual grooming compared to those with lower number of social media accounts (F (2, 191) = 7.30, p = 0.001). Findings also revealed that there was no significant difference on online sexual grooming vulnerability in terms of gender (t (191) = -0.39, p = 0.149). As a conclusion, this study provide in-depth exposure related to online sexual grooming vulnerability to public as well as the urgent need for proactive prevention efforts to curb child sexual related offenses.